Security and Covid-19 The Political and Security System, Regional Security Forecasts and New State Actors Before and During the Pandemic - GJurovski, Marjan; Dronzija, Tatjana; Djukanović, Dragan (Фондација Конрад Аденауер, Канцеларија Скопје Универзитет Св. Климент Охридски – Битола, 2020)
The publication represents a sublimation of shared experiences and conclusions that were presented within the framework of a trilateral initiative on the topic "Regional security challenges and new state actors during and after the crisis of the Covid-19 pandemic", in the framework of which a series of webinars were held in which representatives participated from the academic sphere, i.e. security experts, as well as representatives from the state authorities of the Republic of Macedonia. The publication covers the health crisis with COVID-19 from the aspect of possibilities and perspectives for the regional cooperation of the countries of the region, ie North Macedonia, Bulgaria and Serbia, in the direction of more efficient and successful handling of the consequences of the pandemic.
Keywords: Security and COVID-19: Political-security system, regional security challenges, new state actors , pandemic